Penguatan Akuntabilitas Kerja melalui Pendekatan Profesional, Emosional, dan Spiritual - Thalib, Mohamad Anwar; Paputungan, Vindi; Yunginger, Nabila Putri H.; Basir, Ahmad Fadhil (Sinesia : Jurnal Pengabdian Masyarakat, 2026)
Work accountability is a crucial aspect in improving employee performance, particularly in small and medium enterprises (SMEs). However, in practice, employees’ understanding of accountability is often limited to technical aspects of task completion without deeper awareness of broader responsibilities. This community service activity aims to strengthen employees’ work accountability through an integrated approach covering professional, emotional, and spiritual dimensions. The method used is a descriptive approach through community education, implemented via counseling and simple training activities. Participants were provided with practical case examples related to daily work activities, such as cash management, stock recording, and emotional control in customer service. Data were collected through direct observation and interaction during the activity, while evaluation was conducted qualitatively based on participants’ responses and engagement. The results indicate a significant improvement in employees’ understanding of accountability in a more comprehensive manner. Employees not only became more aware of the importance of accuracy, discipline, and responsibility in work (professional aspect), but also demonstrated better emotional control and awareness of spiritual values such as honesty and integrity. This study concludes that integrating professional, emotional, and spiritual approaches is effective in strengthening work accountability and fostering more responsible, ethical, and meaningful work behavior.